Performance evaluation of two models in the reactive routing protocol in manets - Muthanna Jaafar Abbas; Haider Mohammed Turki Alhilfi; Tole Sutikno (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
Due to the need for the multicast connection required by multimedia applications such as video conferencing and natural disaster management, it was necessary to use a set of portable and connected wireless peripheral devices without the need for infrastructure and without a central router, by use wireless network as "a mobile ad hoc network (MANET) " Despite the difficulties facing this technology in the process of effective guidance and the expansion of the use of such networks, in this type of network because of its applications in the fields of civil and military systems that do not need an infrastructure for the network to provide communication, the researchers specialized in this field have improved the current routing protocols and design new protocols that are appropriate to the challenges that Routing protocols face due to continuous change In network topology over time. In this paper we improved the current routing protocols and design new protocols that are appropriate to the challenges that Routing protocols face due to continuous change In network topology over time. The NS2 simulation environment was used for the purpose of a comprehensive evaluation of the performance of the TORA and AODV routing protocols By using properties of packet delivery fraction and end-to-end delay was calculated.